Colistin resistance among Gram-negative isolates in Nepal: A review - Devkota, Surya Prasad; Paudel, Ashmita (Journal of Biomedical Sciences, 2020)
Background: Colistin resistance among Gram-negative isolates is a tremendous public health problem, and there are very few studies in Nepal about these pathogens. Hence, this review provides comprehensive data on colistin resistance among Gram-negative isolates from various samples in Nepal. Methods: Articles reporting colistin resistance among various Gram-negative isolates from Nepal before July 2019 were selected; analyzed and relevant data was collected. Results: Colistin resistance was low among clinical isolates (less than 6%) in comparison to food and animal isolates (up to 69%). A wide variety of clinical isolates were colistin-resistant in comparison to food and animal isolates. Many of these isolates were highly drug-resistant and also harbored various drug-resistant determinants. Conclusion: Increased colistin resistance among Gram-negative pathogens is a serious concern. Screening of these isolates in clinical settings, animal farms, and food industries, as well as cautious use of colistin in both clinical and animal farms, is imminent.